Malla antigranizo: Efectos sobre el comportamiento de la vid (Vitis vinifera L.) cv. Merlot - Nahuel, Cesar Gabriel; Perez Peña, Jorge Esteban (Ministerio de Agricultura, Ganadería y Pesca, Argentina, 2025)
Poster